2017
DOI: 10.1186/s12870-016-0951-9
|View full text |Cite
|
Sign up to set email alerts
|

Exogenous spermidine improves seed germination of sweet corn via involvement in phytohormone interactions, H2O2 and relevant gene expression

Abstract: BackgroundThe low seed vigor and poor field emergence are main factors that restricting the extension of sweet corn in China. Spermidine (Spd) plays an important role in plant growth and development, but little is known about the effect of Spd on sweet corn seed germination. Therefore the effect of exogenous Spd on seed germination and physiological and biochemical changes during seed imbibition of Xiantian No.5 were investigated in this study.ResultsSpd soaking treatment not only improved seed germination per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
168
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 238 publications
(182 citation statements)
references
References 55 publications
13
168
1
Order By: Relevance
“…This increase could be one of the reasons for the lowest pigeonpea germination rates when using 0.5 mM Spd ( Figure 1C). Moreover, exogenous Spd might have inhibited the stimulatory effects of plant hormones that participate in seed germination, such as gibberellins (GA) and ethylene (ET), or it could have stimulated abscisic acid (ABA), which is a powerful inhibitor of seed germination (Huang et al, 2017). The decrease in the germination rates of both species under salt stress caused by 0.5 mM SA and Spd might have occurred due to the effect of the low or slightly moderate NaCl concentrations used in this study (20 mM -60 mM).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This increase could be one of the reasons for the lowest pigeonpea germination rates when using 0.5 mM Spd ( Figure 1C). Moreover, exogenous Spd might have inhibited the stimulatory effects of plant hormones that participate in seed germination, such as gibberellins (GA) and ethylene (ET), or it could have stimulated abscisic acid (ABA), which is a powerful inhibitor of seed germination (Huang et al, 2017). The decrease in the germination rates of both species under salt stress caused by 0.5 mM SA and Spd might have occurred due to the effect of the low or slightly moderate NaCl concentrations used in this study (20 mM -60 mM).…”
Section: Resultsmentioning
confidence: 99%
“…In fact, the role of SA may vary with the stress level, i.e., moderate or severe, even if there is an interaction between the downstream signals of ROS and SA, in which redox regulation plays a key role (Barba-EspĂ­n et al, 2011). Nevertheless, the concentration of 0.5 mM SA or Spd might have altered the ratio of gibberellin (GA) to abscisic acid (ABA) in the pigeonpea and lab lab under saline stress; these are hormones that modulate seed germination, so when GA is suppressed, germination is stimulated, or when ABA is induced, germination is inhibited (Rajjou et al, 2006;Tan et al, 2013;Huang et al, 2017). The germination inhibition by exogenous SA could be based on oxidative stress.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have also reported the positive impacts on seed germination through Spd priming (Rebecca et al, 2010;Sedagahat and Rahemi, 2011). Recently, it has been shown that Spd soaking can significantly improve seed germination in corn, while exogenous application of cyclohexylamine (CHA; an inhibitor of Spd biosynthesis) resulted in significant inhibition of seed germination and declined seed vigour (Huang et al, 2017). In comparison with control, seeds pre-soaking in polyamine solutions drastically improved the seedling growth.…”
Section: Resultsmentioning
confidence: 99%
“…In our study, DEGs involved in SAMDC and SPMS were expressed in both cultivars, but higher expression levels were observed in KN27-3 than in XLZ38 during seed germination. Multiple studies have demonstrated that Spd is generally correlated with the hypocotyl elongation rate, such as in chickpea [46], corn [47], and in mung bean [48]. Thus, higher expression of SAMDC and SPMS may increase the accumulation of Spd in germinating KN27-3 seeds under chilling conditions.…”
Section: Discussionmentioning
confidence: 98%